2020
DOI: 10.3846/btp.2020.11053
|View full text |Cite
|
Sign up to set email alerts
|

The Sustainable Performance of the Digital Start-Up Company Based on Customer Participation, Innovation, and Business Model

Abstract: The digital-based start-up industry in Indonesia has developed, but with a high failure rate. This research aims at elaborating the relationship between business model, entrepreneurial orientation, innovation, and sustainable performance on the digital start-up companies in Indonesia. The data were collected using offline and online surveys to 206 leaders or founders of digital start-up companies spread throughout Indonesia. Then, the data were then analysed using the structural equation model. The research re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 40 publications
2
35
0
7
Order By: Relevance
“…Some scholars have stated that engaging market actors in the development stage can slow down innovation and negatively influence its endeavors [51], while other scholars, such as Polykarpou and Barret [20], have indicated that shifts in the roles of actors during the co-creation process can create collaboration challenges. However, the findings of this research are in line with those of several scholars, who have indicated the importance of engaging market actors at this stage, in order to enhance product features and innovation sustainability [50,52]. At the commercialization stage, market actors test the launched product to determine initial satisfaction and share any product functionality concerns.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Some scholars have stated that engaging market actors in the development stage can slow down innovation and negatively influence its endeavors [51], while other scholars, such as Polykarpou and Barret [20], have indicated that shifts in the roles of actors during the co-creation process can create collaboration challenges. However, the findings of this research are in line with those of several scholars, who have indicated the importance of engaging market actors at this stage, in order to enhance product features and innovation sustainability [50,52]. At the commercialization stage, market actors test the launched product to determine initial satisfaction and share any product functionality concerns.…”
Section: Discussionsupporting
confidence: 85%
“…When market actors reject a potential solution, the innovation agent will tend to discard the solution and present another one. These findings contradict previous studies in the literature, who viewed market actors as mere data sources that innovation agents control and utilize [25,50]. Guo et al [11], in their single case study, revealed the significance of market actors and explained that aligning innovation with the needs of market actors stimulates their interest and encourages them to become engaged in value co-creation behaviors.…”
Section: Discussionmentioning
confidence: 66%
“…On the whole, domestic research on enterprise performance evaluation has made certain achievements, but there are still some deficiencies: (1) In terms of timeliness, the existing enterprise performance evaluation system is past-oriented and single, mainly for enterprises that have already The economic business that has occurred is confirmed after the fact. (2) In terms of index setting, the evaluation index is still mainly based on financial indicators, and there is a lack of non-financial performance indicators such as customer satisfaction, market share, basic management level, development strategy, social impact, and ecological environment impact. (3) In terms of analysis methods, there is no original evaluation method, which is mostly limited to the improvement of foreign performance evaluation methods, and has not formed an overall performance evaluation theoretical system.…”
Section: Research Status Of Enterprise Performance Evaluationmentioning
confidence: 99%
“…In the context of the new economy, there is both cooperation and competition among enterprises, and the competition form has gradually evolved from individual competition to competition in the entire transaction network. The process of value creation also shows that the behavior of a single enterprise evolves into a network of enterprise members and collaborative activities [2].…”
Section: Introductionmentioning
confidence: 99%
“…Tiutiunyk et al (2021b) cross-country and macroeconomic analysis on the assessment of the impact of digital transformation on macroeconomic stability for EU countries; Petroye et al (2020) effects of information security on the country's image; Małkowska et al (2021) -on the digitalization of society, digitalization of economy and business digitalization; Petrushenko et al (2018) the research, related with business activity regarding the role of FinTech companies in the system of crossborder money transfers in Ukraine. Danarahmanto et al (2020) consider developing the digital start-up company based on customer participation and innovations; Gallo et al (2019) -peculiarities of innovative trends in human resources management of the companies. Challenges and business risks were developed in the study of Yarovenko et al (2021) about the assessing the risks of information and knowledge loss management, within the investigation carried out by Kobushko et al (2021) on aspects of cash management.…”
Section: Literature Reviewmentioning
confidence: 99%